Differences in secretome in culture media when comparing blastocysts and arrested embryos using multiplex proximity assay. (3rd July 2018) - Lindgren, Karin E.; Gülen Yaldir, Fatma; Hreinsson, Julius; Holte, Jan; Kårehed, Karin; Sundström-Poromaa, Inger; Kaihola, Helena; Åkerud, Helena
Abstract: Objectives: The aim of this study was to assess different patterns of the human embryo secretome analysed as protein levels in culture media. Furthermore, analyses to correlate protein levels with quality and timing to development of human embryos were performed. Material and methods: Human day-2 cryopreserved embryos were cultured for four days in an EmbryoScope ® with a time-lapse camera, and embryo quality was evaluated retrospectively. After culture, the media were collected and relative levels of secreted proteins were analysed using Proseek Multiplex Assays. Protein levels were evaluated in relation to timing to development and the ability to form a blastocyst. Results: Specific patterns of timing of development of blastocysts were found, where a difference in time to start of cavitation was found between high- and low-quality blastocysts. There appeared to be a correlation between specific protein patterns and successful formation of morulae and blastocysts. Embryos developing into blastocysts had higher levels of EMMPRIN than arrested embryos, and levels of caspase-3 were lower in high- versus low-quality blastocysts. Also, higher levels of VEGF-A, IL-6, and EMMPRIN correlated with shorter times to morula formation. Conclusions: The secretome and timing to development differ in embryos forming blastocysts and those that become arrested, and in high- versus low-quality blastocysts. The levels of certain proteins also correlate to specific times to development.